Awareness and readiness of gen z university student toward industrial revolution 4.0 technologies - Lee, Weng Zhan (2022)
In today's jargon, "Industrial Revolution 4.0" (IR4.0) refers to a wave of change that will touch all aspects of human existence. IR4.0 technologies and beyond will place increasing demands on the future workforce, which academics must help the new generation (Gen Z) university student prepare for. This paper attempts to investigate the awareness and readiness of Gen Z university student toward the IR4.0 technologies. Research overview, literature review, methodology, data analysis and discussion, conclusion and implications are all covered in this study. The independent and dependent variables have been analyzed in this study, and each variable is explained by referencing previous literature studies. The independent variables are performance expectancy, effort expectancy, social influence, perceived risk and trust, while the dependent variable is Gen Z university student's behavioral intention to use IR4.0 technologies. The research approach chosen would be quantitative research in this study. Besides, primary data were collected through questionnaires with a sample size of 168 respondents who current study in Malaysia's univsersity. The results for descriptive analysis, reliability test, and inferential analysis were obtained through the Statistical Package for the Social Sciences (SPSS). As the result show that all independent variables have significant relationship with the dependent variable. Finally, this research has included the study's limitations as well as future research recommendations to the future researchers.